Globe Hotel and Inner City Poems - Kinsella, John (Vallum Contemporary Poetry, 2012)
In Globe Hotel and Inner City Poems, John Kinsella explores both the physical dimensions and power dynamics of the city. From the "patterns of exclusion" to the "horseshoe bridge" where "gargoyle swans smile like city mascots," Kinsella simultaneously maps the landscape of the city and the unnamed speaker's psyche.